Super-hydrophobic material and preparation method thereof

Through oxidation and precipitation self-assembly technology, the superhydrophobic material with micro-nano structure is constructed, which solves the problems of complex preparation and limited application range of existing superhydrophobic materials, and achieves better superhydrophobic properties.

CN119859290APending Publication Date: 2025-04-22XIAMEN RUIJU MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510115661.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The preparation methods of existing superhydrophobic materials are relatively complex, and the application scope of materials is not wide enough, so improvement is urgently needed.

Method used

The superhydrophobic material with a micro-nano structure is constructed by oxidation and precipitation self-assembly, and a silane coupling agent is added to the poor solvent. During the precipitation self-assembly, the silane coupling agent is adsorbed on the surface of the micro-nano structure and reacted, so that the organic structure with better hydrophobicity is better on the surface chemical bonding graft of the micro-nano structure.

Benefits of technology

The superhydrophobic properties of superhydrophobic materials are improved, so that they can show better hydrophobic properties under the combination of micro-nano structure and low surface energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859290A_ABST
    Figure CN119859290A_ABST
Patent Text Reader

Abstract

The invention provides a super-hydrophobic material and a preparation method thereof, and relates to the technical field of super-hydrophobic materials. The super-hydrophobic material has a micro-nano structure, and is composed of an oxidation-state polymer base material and an organic structure which is located on the surface of the oxidation-state polymer base material and is chemically bonded with the oxidation-state polymer base material. The super-hydrophobic material has good super-hydrophobicity, and the organic structure on the surface can further improve the super-hydrophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of super hydrophobicity and relates to a super hydrophobic material and a preparation method thereof. Background Art

[0002] Super-hydrophobic materials have been applied in many fields, and have great application prospects in many fields, and have become one of the important directions of new material development research. Super-hydrophobic materials are usually obtained by constructing micro-nano structures or using ultra-low surface energy, or a combination of the two methods. For example, Chinese patent CN110452444A discloses a cross-linked polyethylene composite material with super-hydrophobic properties, with low-density polyethylene as the matrix, and mesoporous nano-silica with fluorine-containing functional molecules modified on the surface as the filler, and then cross-linked vulcanization is performed to obtain. Chinese patent CN106496621A discloses a method for making a polyethylene surface super-hydrophobic, comprising the following steps: (1) washing the polyethylene material surface with n-hexane, methanol and deionized water and then air-drying; (2) adding PE-b-PTFE to toluene, heating and stirring to prepare a solution; (3) fixing the polyethylene material on a rotating device, pouring the PE-b-PTFE solution on its surface while it is hot; (4) immediately starting the rotating device and keeping it rotating so that the solution is evenly coated on the polyethylene surface, and then air-drying; (5) annealing under nitrogen protection to achieve super-hydrophobic polyethylene surface.

[0003] However, the current preparation methods of superhydrophobic materials are relatively complicated, and the application range of the materials is not wide enough, so the existing technology urgently needs to be improved. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a super hydrophobic material and a preparation method thereof.

[0005] The technical solution of the present invention is as follows:

[0006] A super hydrophobic material has a micro-nano structure and is composed of an oxidized polymer substrate and an organic structure located on the surface of the oxidized polymer substrate and chemically bonded.

[0007] Preferably, the polymer substrate is selected from homopolymers or copolymers of olefins.

[0008] More preferably, the olefin is selected from one of C2-C8 α-olefins, C4-C8 cycloolefins and C6-C12 substituted cycloolefins.

[0009] Preferably, the organic structure does not contain at least one of an amino group, a carboxyl group, a hydroxyl group, a -COC- structure, -CONH2, an aldehyde group, an ester group, a carbonyl group and a sulfonic acid group.

[0010] Preferably, the structure of the organic structure is as shown in the following formula (1):

[0011] -O 3-x S i 1 x R 2 (1)

[0012] Among them, R 1 is selected from H or C1-C4 alkyl, R 2 Selected from C1-C36 alkyl or F-substituted C3-C18 alkyl, x=0-1.

[0013] A method for preparing the super-hydrophobic material according to any one of the above embodiments, wherein a polymer substrate in a molten state is oxidized and then dissolved in an organic solvent, and then poured into a poor solvent for precipitation, and the solid is collected and dried to obtain the super-hydrophobic material;

[0014] The poor solvent contains a silane coupling agent.

[0015] Preferably, the oxidant used for the oxidation is selected from one or a combination of two or more of oxygen, ozone, organic peroxides, persulfates, hypochlorites and percarbonates.

[0016] Preferably, the structure of the silane coupling agent is as shown in the following formula (2):

[0017] R 1 x R 2 Si(OR 3 ) 3-x (2)

[0018] Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is selected from C1-C36 alkyl or F-substituted C3-C18 alkyl, R 3 Selected from C1-C4 alkyl, x=0-1.

[0019] Preferably, the weight proportion of the silane coupling agent in the poor solvent is 0.1-10%.

[0020] Preferably, the poor solvent is selected from one or a combination of two or more highly polar solvents.

[0021] The beneficial effects of the present invention are as follows: the present invention constructs a super-hydrophobic material with a micro-nano structure through oxidation and precipitation self-assembly, and at the same time, a silane coupling agent is added to a poor solvent. During the precipitation self-assembly process, the silane coupling agent is adsorbed on the surface of the micro-nano structure and reacts, so that an organic structure with good hydrophobicity is chemically bonded and grafted on the surface of the micro-nano structure, thereby further improving the super-hydrophobic performance of the super-hydrophobic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the water drop angle of the superhydrophobic material obtained in Example 1 after being flattened. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0024] On the one hand, the present invention provides a super hydrophobic material having a micro-nano structure, and the super hydrophobic material is composed of an oxidized polymer substrate and an organic structure located on the surface of the oxidized polymer substrate and chemically bonded.

[0025] The super-hydrophobic material of the present invention has a micro-nano structure, and its constituent materials mainly come from an oxidized polymer substrate, and an organic structure is chemically bonded to the surface of the oxidized polymer substrate, and the organic structure can provide a lower surface energy. The super-hydrophobic material of the present invention combines the characteristics of the micro-nano structure and the low surface energy, so that the super-hydrophobic performance of the super-hydrophobic material is better.

[0026] In the present invention, the oxidized polymer substrate refers to the polymer substrate being oxidized and generating oxygen-containing groups such as hydroxyl, carboxyl, carbonyl, etc. on the polymer chain. The oxygen-containing groups on the surface of the oxidized polymer substrate are highly active and can react and introduce organic structures to further improve the superhydrophobic performance.

[0027] In a preferred embodiment of the present invention, the polymer substrate is selected from homopolymers or copolymers of olefins. In the present invention, olefins are not particularly limited, including olefins with chain structures and olefins with cyclic structures. More preferably, the olefin is selected from one of C2-C8 α-olefins, C4-C8 cycloolefins and C6-C12 substituted cycloolefins. For example, α-olefins are olefins with chain structures, which can be ethylene, propylene, 1-butene, 1-hexene, 1-octene, etc. The olefins with cyclic structures can be 1-cyclobutene, 3-methylcyclobutene, cyclopentene, cyclohexene, etc. For example, the polymer substrate can be polyethylene, polypropylene, ethylene / 1-butene copolymer, ethylene / 1-octene copolymer, propylene / cyclobutene copolymer, etc.

[0028] In a preferred embodiment of the present invention, the organic structure does not contain at least one of amino, carboxyl, hydroxyl, -COC-structure, -CONH2, aldehyde, ester, carbonyl and sulfonic acid groups. In the present invention, the purpose of chemically bonding the organic structure on the surface of the polymer substrate in an oxidized state is to improve hydrophobicity, if the organic structure contains a good hydrophilic group, such as the amino, carboxyl, hydroxyl, -COC-structure (ether bond), -CONH2, aldehyde, ester, carbonyl and sulfonic acid groups listed above, it will be unfavorable for the hydrophobic promotion of super-hydrophobic material, and may reduce the hydrophobicity of super-hydrophobic material instead.

[0029] More preferably, the structure of the organic structure is as shown in the following formula (1),

[0030] -O 3-x S i 1 x R 2 (1)

[0031] Among them, R 1 is selected from H or C1-C4 alkyl, R 2 Selected from C1-C36 alkyl or F-substituted C3-C18 alkyl, x=0-1.

[0032] The organic structure shown in the above formula (1) mainly plays a hydrophobic role. 2 , R 2 When it is an alkane or a fluorine-substituted alkane, it has a significant effect on improving the hydrophobicity. 2 When the carbon chain is shorter, such as C1-C4 alkyl, R 1 It can also play a role in improving the hydrophobic properties. 2 It can be n-butyl, n-hexyl, n-octyl, isooctyl, lauryl, stearyl, eicosyl, tetracosyl, or -CH2CH2(CF2) n CF3 organic fluorine group, etc., wherein n = 0-12. 2 When it is an organic fluorine group, the superhydrophobic material can achieve a lower surface energy, and the effect of improving the superhydrophobic performance is more obvious.

[0033] On the other hand, the present invention provides a method for preparing a super-hydrophobic material according to any one of the above embodiments, wherein a molten polymer substrate is oxidized and dissolved in an organic solvent, and then poured into a poor solvent for precipitation, and the solid is collected and dried to obtain a super-hydrophobic material;

[0034] The poor solvent contains a silane coupling agent.

[0035] In the present invention, a polymer substrate in a molten state is adopted, and the polymer substrate in a molten state has good fluidity, is more likely to contact and mix evenly with the oxidant used for oxidation, and the polymer substrate temperature in a molten state is high, and the oxidant is more likely to oxidize it. After the polymer substrate is oxidized by the oxidant, the macromolecular chain will produce organic groups such as hydroxyl, carboxyl, carbonyl, etc., and has higher reactivity. The micro-nano structure of the super-hydrophobic material of the present invention is formed by precipitation and self-assembly in a poor solvent. When a silane coupling agent is contained in a poor solvent, the polarity of the alkoxysilyl (or the silanol produced by hydrolysis) on the silane coupling agent is strong and active, and the oxygen-containing organic groups such as hydroxyl, carboxyl produced by oxidation reaction can be adsorbed and further reacted due to the effects of hydrogen bonds, van der Waals forces, etc., so that the organic structure in the silane is chemically bonded to the surface of the polymer substrate in the oxidized state of the micro-nano structure, and the super-hydrophobic performance is further improved.

[0036] In the present invention, the melting temperature of the polymer substrate in the molten state is not particularly limited, and can be the melting processing temperature during twin-screw extrusion. For example, for polyethylene, the melting temperature can be 190-220°C, for polypropylene, the melting temperature can be 220-250°C, and for ethylene / 1-butene copolymer, the melting temperature can be 160-190°C.

[0037] In a preferred embodiment of the present invention, the oxidant used for oxidation is selected from one or a combination of two or more of oxygen, ozone, organic peroxide, persulfate, hypochlorite and percarbonate. Different oxidants have different oxidizing abilities and addition methods, so the amount of oxidant, oxidation reaction time, etc. are also different. For gaseous oxidants, such as oxygen and ozone, a method of continuously passing them into the molten polymer substrate is usually adopted. For liquid and solid oxidants, a method of first mixing with the polymer substrate and then melting them together is usually adopted. In order to improve the oxidation effect and efficiency, a combination of two or more oxidants can also be adopted to synergistically exert the oxidizing properties of two or more oxidants, such as a combination of oxygen and organic peroxide, a combination of oxygen and persulfate, a combination of oxygen and percarbonate, a combination of organic peroxide and persulfate, a combination of persulfate and hypochlorite, etc. In the present invention, the weight of the oxidant added during oxidation is not particularly limited, and can be 0.2-5% of the weight of the polymer substrate. For example, organic peroxides may be diisopropylbenzene peroxide, tert-butyl hydroperoxide, methyl ethyl ketone peroxide, isobutyl methyl ketone peroxide, bis-2,4, bis-2,5, etc., persulfates may be ammonium persulfate, sodium persulfate, potassium persulfate, etc., hypochlorites may be sodium hypochlorite, potassium hypochlorite, etc., and percarbonates may be ammonium percarbonate, sodium percarbonate, potassium percarbonate, etc. Depending on the amount of oxidant added and the temperature of the oxidation reaction, the oxidation reaction time may be adjusted accordingly, for example, it may be 0.5-24h. Generally, the higher the oxidation reaction temperature and the more oxidant added, the shorter the oxidation reaction time. In order to improve the oxidation efficiency, a certain amount of accelerator may be added to the olefin polymer resin, such as benzyl chloride, triphenylmethane, diphenylmethane, etc., and the amount of the accelerator may be 20-100% of the amount of the oxidant.

[0038] In a preferred embodiment of the present invention, the structure of the silane coupling agent is shown in the following formula (2):

[0039] R 1 x R 2 Si(OR 3 ) 3-x (2)

[0040] Among them, R 1is selected from H or C1-C4 alkyl, R 2 is selected from C1-C36 alkyl or F-substituted C3-C18 alkyl, R 3 Selected from C1-C4 alkyl, x=0-1.

[0041] The alkoxysilyl group of the silane coupling agent or the silanol group generated by hydrolysis has a high reactivity and can react with a hydroxyl group, a carboxyl group, etc. For example, the silane coupling agent of the present invention can be n-butyltrimethoxysilane, n-octyltrimethoxysilane, isooctyltrimethoxysilane, n-octyltriethoxysilane, n-octylmethyldimethoxysilane, lauryltrimethoxysilane, laurylmethyldimethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, 3,3,3-trifluoropropylmethyldimethoxysilane, 3,3,3-trifluoropropyltriethoxysilane, perfluorohexylethyltrimethoxysilane, perfluorooctylethyltrimethoxysilane, etc.

[0042] In a preferred embodiment of the present invention, the weight proportion of the silane coupling agent in the poor solvent is 0.1-10%. For example, the weight proportion of the silane coupling agent in the poor solvent can be any value of 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., without special restrictions. Further, the weight proportion of the silane coupling agent in the poor solvent can be 1-6%. When the weight proportion of the silane coupling agent in the poor solvent exceeds 6%, continuing to increase the weight proportion of the silane coupling agent has no obvious effect on the formation of an organic structure on the surface of the micro-nano structure, which is not economically preferred.

[0043] In a preferred embodiment of the present invention, the poor solvent is selected from one or a combination of two or more of the high polar solvents. The polarity of the oxidized polymer substrate is still relatively low, and the compatibility with the high polar solvent is poor, so the high polar solvent can be used as a poor solvent for the oxidized polymer substrate and as a solvent for the silane coupling agent. In the present invention, there is no particular restriction on the high polar solvent, and the dielectric constant at 20°C is not less than 16. For example, it can be water and / or a high polar organic solvent, and the high polar organic solvent can be acetone, methanol, ethanol, acetone, methyl ethyl ketone, ethylene glycol dimethyl ether, ethylene glycol monomethyl ether, butyl acetate, etc. When the polarity of the oxidized polymer substrate is relatively high, a solvent with higher polarity can be used, such as water, methanol, etc. More preferably, the poor solvent is a combination of water and a high polar organic solvent, such as a combination of water and acetone in a weight ratio of 1:1-5, a combination of water and methanol in a weight ratio of 1:1-10, a combination of water and ethanol in a weight ratio of 1:1-10, etc. The poor solvent contains water, which helps the hydrolysis of the silane coupling agent to form silanol groups, and has high adsorption and reactivity with the oxidized polymer substrate. After adsorption, the reaction can be further completed when drying.

[0044] In the present invention, there is no particular restriction on the organic solvent, and it is preferred that the organic solvent has good solubility for the oxidized polymer substrate. It can be selected from one or a combination of two or more of non-polar organic solvents and low-polar organic solvents. The dielectric constant of non-polar organic solvents and low-polar organic solvents at 20°C does not exceed 12, and it will not or is difficult to undergo proton self-transfer reaction, nor will it undergo solvation with the oxidized polymer substrate. For example, it can be benzene, toluene, xylene, cyclohexane, petroleum ether, dichloromethane, 1,2-dichloroethane, carbon tetrachloride, etc. More preferably, the dielectric constant of non-polar organic solvents and low-polar organic solvents at 20°C does not exceed 5, and can be toluene, xylene, cyclohexane, n-hexane, petroleum ether, etc. There is no particular restriction on the weight ratio of the polymer substrate and the organic solvent, and preferably, the weight ratio can be 1-20:10. There is no particular restriction on the volume ratio of the organic solvent and the poor solvent, and preferably, the volume ratio can be 1:5-50.

[0045] In the present invention, the drying temperature is not particularly limited, and preferably does not exceed the softening temperature of the super-hydrophobic material, and can be room temperature to 60°C.

[0046] The technical solution of the present invention is further described and illustrated according to various embodiments below.

[0047] Example 1

[0048] 100 g of polypropylene (230°C, 2.16 kg load, melt index 5 g / 10 min) and 1 g of potassium persulfate were added to the reactor, the temperature was raised to 240°C under nitrogen protection, and stirred for 5 h. The temperature was lowered to no more than 50°C, 100 g of toluene was added, stirred to dissolve evenly, and then slowly poured into 2000 g of a poor solvent for precipitation. The precipitated particles were collected and dried at 60°C for 5 h to obtain a superhydrophobic material.

[0049] 2000 g of the poor solvent consists of 400 g of water, 1598 g of methanol and 2 g of n-octyltrimethoxysilane.

[0050] The schematic diagram of the water drop angle after the super hydrophobic material obtained in this embodiment is flattened is shown in the attached figure. Figure 1 shown.

[0051] Example 2

[0052] The difference between this embodiment and embodiment 1 is that in embodiment 1, 2000 g of the poor solvent is adjusted to consist of 400 g of water, 1580 g of anhydrous ethanol and 20 g of n-octyltrimethoxysilane. The other steps remain unchanged.

[0053] Example 3

[0054] The difference between this embodiment and embodiment 1 is that in embodiment 1, 2000 g of the poor solvent is adjusted to consist of 400 g of water, 1480 g of methanol and 120 g of n-octyltrimethoxysilane. The other steps remain unchanged.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 2 is that in embodiment 2, n-octyltrimethoxysilane is adjusted to an equal weight of 3,3,3-trifluoropropyltrimethoxysilane. The remaining steps remain unchanged.

[0057] Example 5

[0058] The difference between this embodiment and embodiment 2 is that in embodiment 2, n-octyltrimethoxysilane is adjusted to an equal weight of perfluorohexylethyltrimethoxysilane. The remaining steps remain unchanged.

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 1 is that in Example 1, 2000 g of the poor solvent is adjusted to consist of 400 g of water and 1600 g of methanol. The remaining steps remain unchanged.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that in Example 1, 2000 g of the poor solvent is adjusted to consist of 1840 g of anhydrous ethanol and 160 g of stearic acid. The remaining steps remain unchanged.

[0063] Example 6

[0064] 100g POE polyolefin elastomer (melt index 5g / 10min) and 1g potassium persulfate were added to the reactor, heated to 150°C under nitrogen protection and stirred for 8h, oxygen was continuously introduced during the stirring process, the oxygen flow rate was 10ml / min, and the pressure was 0.12MPa. After the reaction was completed, the temperature was lowered to no more than 50°C, 200g toluene was added, stirred and dissolved uniformly, and then slowly poured into 4000g poor solvent for precipitation, the precipitated particles were collected, and dried at 60°C for 5h to obtain a super hydrophobic material.

[0065] 4000 g of the poor solvent consists of 600 g of water, 3320 g of anhydrous ethanol and 80 g of perfluorobutylethyltrimethoxysilane.

[0066] Example 7

[0067] 100g of terpolymer polypropylene (copolymerized by propylene, ethylene and 1-butene), 1g of potassium persulfate and 1g of sodium percarbonate were added to the reactor, and the temperature was raised to 210°C under nitrogen protection and stirred for 6h. After the reaction was completed, the temperature was lowered to no more than 50°C, and a solvent consisting of 100g of cyclohexane and 100g of toluene was added, stirred and dissolved evenly, and then slowly poured into 4000g of a poor solvent for precipitation, the precipitated particles were collected, and dried at 60°C for 5h to obtain a super hydrophobic material.

[0068] 4000 g of the poor solvent consists of 600 g of water, 3320 g of anhydrous ethanol and 80 g of lauryltrimethoxysilane.

[0069] Example 8

[0070] The difference between this embodiment and embodiment 7 is that in embodiment 7, n-octyltrimethoxysilane is adjusted to an equal weight of perfluorooctylethyltrimethoxysilane. The remaining steps remain unchanged.

[0071] Performance Testing

[0072] Water drop angle: measured using a water contact angle tester.

[0073] Roll angle: tested using the inclined surface method.

[0074] The results are shown in Table 1 below.

[0075] Table 1

[0076] Water drop angle / ° Roll angle / ° Water drop angle / ° Roll angle / ° Example 1 155.9 3.0 Comparative Example 1 152.5 4.2 Example 2 158.3 2.5 Comparative Example 2 150.3 7.6 Example 3 160.1 2.2 Example 6 160.6 1.8 Example 4 161.4 1.7 Example 7 159.2 2.3 Example 5 163.5 1.1 Example 8 165.0 0.9

[0077] It can be seen from the data results in Table 1 that the present invention can further improve the superhydrophobic property of the superhydrophobic material by adding a silane coupling agent to a poor solvent and chemically bonding an organic structure with good hydrophobicity on the surface of the micro-nano structure after precipitation and self-assembly.

[0078] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A super hydrophobic material, characterized in that: The super hydrophobic material has a micro-nano structure and is composed of an oxidized polymer substrate and an organic structure located on the surface of the oxidized polymer substrate and chemically bonded.

2. The super hydrophobic material according to claim 1, characterized in that The polymer substrate is selected from homopolymers or copolymers of olefins.

3. The super hydrophobic material according to claim 2, characterized in that The olefin is selected from one of C2-C8 α-olefins, C4-C8 cycloolefins and C6-C12 substituted cycloolefins.

4. The super hydrophobic material according to claim 1, characterized in that The organic structure does not contain at least one of an amino group, a carboxyl group, a hydroxyl group, a -COC- structure, -CONH2, an aldehyde group, an ester group, a carbonyl group and a sulfonic acid group.

5. The super hydrophobic material according to claim 1, characterized in that The structure of the organic structure is shown in the following formula (1): -O 3-x SiR 1 x R 2 (1) Among them, R 1 is selected from H or C1-C4 alkyl, R 2 Selected from C1-C36 alkyl or F-substituted C3-C18 alkyl, x=0-1.

6. A method for preparing a super-hydrophobic material according to any one of claims 1 to 5, characterized in that: The polymer substrate in a molten state is oxidized and then dissolved in an organic solvent, and then poured into a poor solvent for precipitation, and the solid is collected and dried to obtain the super hydrophobic material; The poor solvent contains a silane coupling agent.

7. The method for preparing a super hydrophobic material according to claim 6, wherein The oxidant used for the oxidation is selected from one or a combination of two or more of oxygen, ozone, organic peroxide, persulfate, hypochlorite and percarbonate.

8. The method for preparing a super hydrophobic material according to claim 6, wherein The structure of the silane coupling agent is shown in the following formula (2): R 1 x R 2 Si(OR 3 ) 3-x (2) Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is selected from C1-C36 alkyl or F-substituted C3-C18 alkyl, R 3 Selected from C1-C4 alkyl, x=0-1.

9. The method for preparing a super hydrophobic material according to claim 6, wherein The weight proportion of the silane coupling agent in the poor solvent is 0.1-10%.

10. The method for preparing a super hydrophobic material according to claim 6, wherein: The poor solvent is selected from one or a combination of two or more highly polar solvents.

Citation Information

Patent Citations

  • Polyethylene surface hydrophobization method

    CN106496621A

  • Crosslinked polyethylene composite material with super-hydrophobic property and preparation method and application

    CN110452444A